2016
DOI: 10.1073/pnas.1524813113
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional manipulation of single cells using surface acoustic waves

Abstract: The ability of surface acoustic waves to trap and manipulate micrometer-scale particles and biological cells has led to many applications involving "acoustic tweezers" in biology, chemistry, engineering, and medicine. Here, we present 3D acoustic tweezers, which use surface acoustic waves to create 3D trapping nodes for the capture and manipulation of microparticles and cells along three mutually orthogonal axes. In this method, we use standing-wave phase shifts to move particles or cells in-plane, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
381
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 508 publications
(384 citation statements)
references
References 28 publications
3
381
0
Order By: Relevance
“…Similar to reports in the literature, 7,8,13,14 when the two orthogonal pairs of IDTs are supplied with the signal simultaneously, the microparticles aggregate at the nodes to form 2D horizontal patterns. Because the intersection of two orthogonal pressure lines forms a pressure node, the microparticles form 2D matrix patterns under the bidirectional acoustic radiation force.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Similar to reports in the literature, 7,8,13,14 when the two orthogonal pairs of IDTs are supplied with the signal simultaneously, the microparticles aggregate at the nodes to form 2D horizontal patterns. Because the intersection of two orthogonal pressure lines forms a pressure node, the microparticles form 2D matrix patterns under the bidirectional acoustic radiation force.…”
supporting
confidence: 75%
“…Precise control of microparticles on the horizontal (xy) plane is easily realized and has been reported variously. 8,14 Herein, we have demonstrated that the vertical positions of microparticles can be controlled precisely and manipulated by adjusting the input power.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a noninvasive and noncontact manipulation method, acoustic trapping has the advantage that it is able to simply levitate many kinds of objects from small living animal to bacteria 15, 16, 17, 18, 19, 20, 21. More importantly, the penetration of sound wave is much deeper than light in nontransparent media.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the penetration of sound wave is much deeper than light in nontransparent media. In addition, acoustic trapping has been demonstrated the ability to restrict objects on the scale of large populations 19, 20. Techniques to achieve this goal are usually based on acoustic radiation force under a certain type of acoustic field, especially using counter‐propagating waves to set up standing wave nodes to trap the particles 15, 17, 21, 22, 23, 24.…”
Section: Introductionmentioning
confidence: 99%